Development and in vitro evaluation of acelofenac mouth dissolving films for reduced analgesic activity - Chandra Sekhar Naik D; Bharathi Arigela; Venkata Suresh Babu Agala; Cherukuri Vidyulatha Chowdary (Creative Pharma Assent, 2024)
Background: The design of the current research work was to formulate mouth-dissolving films (MDFs) of aceclofenac (ACF) to improve patient compliance and convenience for older and younger patients, ultimately leading to improved therapeutic outcomes. Method: Evaluations were conducted on film formers such as HPMC and MC and film modifiers such as PEG and starch acting as solubilizing agents. Results: The physicomechanical qualities, in vitro disintegration time, and in vitro dissolving characteristics of the produced MDFs were assessed. Good mechanical qualities, including as tensile strength, folding durability, and percentage elongation, were demonstrated by every created MDF. FTIR, SEM, and X-RD analyses were used to assess MDFs. In contrast to other formulations, MDFs containing F8 provided superior dissolving properties. Conclusion: When pitted against other mixtures, the MDFs with sodium alginate (5%), methylcellulose (5%), and hydroxypropyl methylcellulose (HPMC)(5%) showed superior dissolving capabilities. In contrast to other mixtures, the F8 mixture, including HPMC, sodium alginate, and methylcellulose, demonstrated a complete and accelerated dissolution within 50 seconds. The mechanism behind this release is diffusion, as indicated by the release kinetics data.